STRATEGI BANK SYARIAH DALAM MENYELESAIKAN PERMASALAHAN PADA PEMBIAYAAN SYARIAH - Agung Zulkarnain Alang (Jurusan Bimbingan dan Penyuluhan Islam, 2022)
The purpose of this paper is to review the strategies used in solving problematic financing in Islamic banks. Islamic banks as financial institutions that are currently facing such rapid growth, in distributing financing to customers cannot be separated from various risks, one of which is nonperforming financing which results in shrinking the level of bank liquidity health, as well as affecting the shrinking level of confidence of customers who entrust their money. In the matter of bad financing, the bank needs to carry out rescue, so it does not want to cause losses. The rescue is carried out whether by distributing relief in the form of a period or the most important installment for disaster financing or by making foreclosures for planned financing that is negligent to pay. Financing that faces congestion should be rescued so that banks do not face losses. However, if it is not possible to carry out the rescue until the next step taken is a settlement process, it can be through Arbitration, the Legal Tribunal or the legal body is linked to the financing settlement.